PENGARUH BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA - Komariah, Diah; Yogiantoro, Mukhammad; Hukom, Alexandra (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The main purpose of the research is to examine the influence of capital expenditure and economic growth on the human development index (HDI) in Kotawaringin Timur Regency from the period of 2009-2017. The research approach is quantitative descriptive by using secondary data collected from the Central Bureau of Statistics (BPS) Kotawaringin Timur Regency. The method used in this study is multiple linear regression using the IBM SPSS version 25.0 application. The results show that partially, capital expenditure took effect positively and significantly, toward HDI, economic growth took effect positively significantly toward HDI. Simultaneously, capital expenditure and economic growth took effect positively and significantly toward HDI. This finding implies the importance of government expenditure on public sectors can stimulate economic growth that provides access to the poor in productive sectors that can increase their well-being. Keywords: Capital Expenditure, Economic Growth, and Human Development Index